Evaluation of Family Service Program, Home Economics Division of Cooperative Extension, Essex County, New York Extension Study No. 19 - Alexander, Frank D.; Cornell Univ., Ithaca, NY. Cooperative Extension Service ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
An evaluation study of the Family Service Program of the Essex County (New York) Division of Home Economics is focused on the third series of lessons; the purposes of the study were to describe the socioeconomic characteristics of the indigenous program aides and the participants and to show the influence of training for teaching this series of lessons. It was found that aides had higher income, participation scores, and educational levels than participants, but both groups were low in comparison to the country's total population in level of husband's occupation, net family income, and years of school completed. Both aides and participants made significant gains from the pre- to posttest while aides showed slightly higher scores in both testing situations. Participants listed problems of cooking and planning meals, housekeeping, and money management, while aides identified participant problems of care and discipline of children, and health. Among implications are that indigenous women make effective teachers of home economics; both participants in study groups and those taught alone make significant progress; and closer supervision of teaching and attendance would improve the program. (pt)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Family Problems; Indigenous Personnel; Participant Characteristics; Questionnaires; Teacher Effectiveness; Tests; Disadvantaged; Family Life Education; Program Evaluation; Rural Extension; Teacher Aides; New York